High-Efficiency and Narrowband Green Thermally Activated Delayed Fluorescence Organic Light-Emitting Diodes Based on Two Diverse Boron Multi-Resonant Skeletons - Zhen Wang; Cheng Qu; Jie Liang; Xuming Zhuang; Yu Liu; Yue Wang (Molecules, 2024)
Up to now, highly efficient narrowband thermally activated delayed fluorescence (TADF) molecules constructed by oxygen-bridged boron with an enhancing multiple resonance (MR) effect have been in urgent demand for solid-state lighting and full-color displays. In this work, a novel MR-TADF molecule, BNBO, constructed by the oxygen-bridged boron unit and boron–nitrogen core skeleton as an electron-donating moiety, is successfully designed and synthesized via a facile one-step synthesis. Based on BNBO as an efficient green emitter, the organic light-emitting diode (OLED) shows a sharp emission peak of 508 nm with a full-width at half-maximum (FWHM) of 36 nm and realizes quite high peak efficiency values, including an external quantum efficiency (EQEmax) of 24.3% and a power efficiency (PEmax) of 62.3 lm/W. BNBO possesses the intramolecular charge transfer (ICT) property of donor-acceptor (D-A) materials and multiple resonance characteristics, which provide a simple strategy for narrowband oxygen–boron materials.